Effects of E-genes and photoperiod duration on assimilation processes in isogenic lines of soybean - Yukhno, Yulia; Zhmurko, Vasyl (ScienceRise: Biological Science, 2021)
The aim of the research. To reveal the patterns of genetic control of assimilation processes in isogenic by E-genes lines of soybean conditions of different photoperiod duration. Materials and methods. The plant material – 5 isolines of soybean (Glycine max (L.) Merr.) Cv. Clark: short-day (SD) lines (genotypes E1E2E3, E1e2e3) and neutral-day (ND) lines (genotypes e1E2e3, e1e2E3, e1e2e3). From the third true leaf stage, one part of the plants was grown on a natural day (16 hours), and the other was exposed to a short day (9 hours). On the day of the start of the experiment, after 7 and 14 days, the dry weight of leaves and stems, the number and area of leaves were measured, based on which assimilation indices were calculated – RGR, NAR, LAR, SLA, LWR. Results. During the studied ontogenetic period (two weeks) in all isolines, regardless of the genotype by E-genes and the duration of the photoperiod, the assimilation processes increased. The RGR and NAR under the short day decreased in the first week and then increased in the second week of the experiment. The degree of change in the indices varied depending on the isoline genotype by E-genes. The LAR and LWR were lower under the short day in SD lines. These indices were the same in the ND lines under short and long day. Under the short photoperiod the SLA in SD lines was higher, and in ND lines it was practically the same for both photoperiods. Conclusions. The assimilation processes in the studied isogenic lines during the experience (two weeks) increase, but less intensively under short-day conditions. The studied lines, differed in the nature and intensity of assimilation processes, depending on the genotype by E-genes. Assimilation processes in the studied soybean lines are probably determined by the interaction of E-genes and the duration of the photoperiod, which is one of the important conditions for the adaptation of soybean to the environmental factors